Tantangan Dan Peluang Percepatan Pengembangan BUMDES Menuju Status Berkembang Dan Maju Di Kabupaten Cilacap - Putri Yuni Astuti; Yuri Fitriyani Tamala; Ade Yunita Mafruhat (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
Cilacap Regency has 269 villages. The existence of Village Owned Enterprises (BUMDes) is expected to accelerate the development of village potential that is able to improve the community's economy. This research uses qualitative descriptive and focuses on the challenges and opportunities of accelerating bumdes development towards developing status and advanced status. The results of this study show that most BUMDes in Cilacap Regency have various obstacles that have the potential to become an obstacle in the management of BUMDes. Problems for the management of BUMDes are found in all dimensions through bumdes development criteria, namely: 1) limited market coverage, 2) capital limitations, and 3) assets. Meanwhile, from the criteria that there is a growing status and advanced status, which is a weakness point in the asset indicator. This is a difficulty to carry out new business development and limited innovation in building local products.